In Search of Our True Selves: Feedback as a Path to Self-Knowledge - Bollich, Kathryn L.; Johannet, Paul M.; Vazire, Simine (Frontiers in Psychology, 2011)
How can self-knowledge of personality be improved? What path is the most fruitful source for learning about our true selves? Previous research has noted two main avenues for learning about the self: looking inward (e.g., introspection) and looking outward (e.g., feedback). Although most of the literature on these topics does not directly measure the accuracy of self-perceptions (i.e., self-knowledge), we review these paths and their potential for improving self-knowledge. We come to the conclusion that explicit feedback, a largely unexamined path, is likely a fruitful avenue for learning about one’s own personality. Specifically, we suggest that self-knowledge might be fully realized through the use of explicit feedback from close, knowledgeable others. As such, we conclude that the road to self-knowledge likely cannot be traveled alone but must be traveled with close others who can help shed light on our blind spots.